Virtual Reality Feedback Cues for Improvement of Gait in Patients with Parkinson's Disease. (1st April 2014) - Badarny, Samih; Aharon-Peretz, Judith; Susel, Zvi; Habib, George; Baram, Yoram
Background: Our aim was to study the effects of visual feedback cues, responding dynamically to patient's self-motion and provided through a portable see-through virtual reality apparatus, on the walking abilities of patients with Parkinson's disease. Methods: Twenty patients participated. On-line and residual effects on walking speed and stride length were measured. Results: Attaching the visual feedback device to the patient with the display turned off showed a negligible effect of about 2%. With the display turned on, 56% of the patients improved either their walking speed, or their stride length, or both, by over 20%. After device removal, and waiting for 15 minutes, the patients were instructed to walk again: 68% of the patients showed over 20% improvement in either walking speed or stride length or both. One week after participating in the first test, 36% of the patients showed over 20% improvement in baseline performance with respect to the previous test. Some of the patients reported that they still walked on the tiles in their minds. Discussion: Improvements in walking abilities were measured in patients with Parkinson's disease using virtual reality visual feedback cues. Residual effects suggest the examination of this approach in a comprehensive therapy program.